Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. Students’ Attitudes at UNRWA’s University College for Educational Sciences in Palestine Toward Electronic Tests from their own Points of View Dr. Jamal Mohammad Marshood , Mrs. Iman Mostafa Hamoda , Mrs. Duha Sami Mufreh , Mrs. Fatin Adel Ayyash , Mrs. Nujood Ayed Hamduni 2. The role of university administration in spreading the entrepreneurship culture among students of Prince Satam bin Abdulaziz University and the obstacles to activating it from the viewpoint of the university administration Mrs. Amal Farhan Nasser Al-Dosari , Dr. Abdul Aziz Muhammad Al-Saqer 3. Territorial Governance and Competencies of Managing the Territory in the Moroccan Primary Education Curriculum Mrs. Rachida Allal AOUIDATE, Prof. Mustapha AAFIR , Prof. Abd Elouahed Boubria 4. The Extent to which Teachers of Deaf and Hard of Hearing Students in the Primary Stage use Augmented Reality Applications and the Barriers they Face Mr. Mohammed Saleh Alghamdi, Dr. Turki Samah Alzahraney 5. The Role of Sustainable Leadership in Achieving Professional Motivation at the Education Offices in Riyadh Mrs. Bayan Saud Al-Zaid 6. Methods of coping with stress and its relationship to the quality of family life to a sample of mothers of deaf and hard of hearing children in the western region of the Kingdom of Saudi Arabia Mrs. Dhuha Omar Almaghrabi 7. Impact of a collective mentorship programmer on reducing depression and improving the self-esteem of Syrian female students in the Za ’atari camp Mrs. Na’ela Odeh Abedalqader Keelani